Kazakhstan Country Economic Update, Spring 2018 : The Quest for a New Growth Model–The Urgency of Economic Transformation - World Bank Group (World Bank, Washington, DC, 2018)
A recovery in the oil sector boosted recent economic performance. While the recovery in global oil prices would have a welcoming effect for Kazakhstan in terms of enhancing the economy’s buffers and supporting growth, it may also reduce the perceived urgency for transitioning to the new growth model, including the strong need of continuing the macro-fiscal adjustment (by reducing the nonoil deficit over the medium term) and pressing ahead with structural reforms. More generally, a return to any procyclical macro-fiscal policies during the upswing (due to an insufficient fiscal consolidation) risks developing a Dutch-Disease type of episode that could reduce economy’s competitiveness and lower opportunities for diversification away from oil and other non-tradable goods and services with dynamics positively correlated to oil price movements. The authorities should not miss the current window of opportunity to adjust the macro-fiscal framework, clean up the banking sector, and deepen structural reforms. To transit to a new growth model and facilitate a sizeable expansion of the tradable nonoil sector’s role in the economy, the government must demonstrate significant improvements to the rule of law, the quality of human capital, and the investment climate.